Tooth Eruption without Roots - Wang, X.-P. (SAGE Publications, 2013)
Root development and tooth eruption are very important topics in dentistry. However, they remain among the less-studied and -understood subjects. Root development accompanies rapid tooth eruption, but roots are required for the movement of teeth into the oral cavity. It has been shown that the dental follicle and bone remodeling are essential for tooth eruption. So far, only limited genes have been associated with root formation and tooth eruption. This may be due to the difficulties in studying late stages of tooth development and tooth movement and the lack of good model systems. Transgenic mice with eruption problems and short or no roots can be used as a powerful model for further deciphering of the cellular, molecular, and genetic mechanisms underlying root formation and tooth eruption. Better understanding of these processes can provide hints on delivering more efficient dental therapies in the future.